Relasi Gender dalam Kolom Humor â€œSi Paluiâ€ di Banjarmasin Post (Analisis Wacana Kritis Norman Fairclough pada Kolom Humor Si Palui di Banjarmasin Post) - Vidiadari, Irene Santika (Universitas Muhammadiyah Ponorogo, 2017)
As well as a result of cultural perception, humour can also be seen as a kind of text representing the culture of society which produces it. The humour column of â€œSi Paluiâ€ in Banjarmasin Post is not an exception. Reflecting the culture of the people of Banjar, the stories in Si Palui are strongly related to women and how men, as the dominant gender in Banjar culture, deal with women in daily life. Inasmuchas text is firmly connected with discourse, using Norman Faircloughâ€™s Critical Discourse Analysis, in this paper I will see the discourse of gender relation in Si Palui on three levelsâ€”micro (text), mezzo (text producent), and macro (sociocultural). On micro level the representation is seen from the using of language. On the second level, mezzo, how women are represented is studied from the view point of the text producent, namely Banjarmasin Post. Meanwhile on the third level which is macro, the representation of women in Si Palui is comprehended from broader perspective, namely the Banjar culture which can not be separated from Islam Banjar. It is concluded from this research that: (1) On micro level men are always more dominant than women, (2) on mezzo level the sexist humor of Si Palui is strongly related to the fact that all of the writer of Si Palui are men, and (3) on macro level, the gender relation narrated on Si Palui is firmly connected with patriarchal ideology adopted by the people of Banjar, which is legitimated by Islam Banjar.